A CIÊNCIA NO PICADEIRO: UMA ANÁLISE DAS REPORTAGENS SOBRE CIÊNCIA NO PROGRAMA FANTÁSTICO - Rondelli, Daniella Rubbo Rodrigues (2004)
This work intends to make one critical analysis of the discuss about science in the Fantástico television program. By the critical analysis perspective, the work tries to find signs that show the intention of both scientists and communicators discuss as well as the differences between the intention and the effective communication, as every communicative act is full of the conditions in that it was made and received. The work identifies the program as an enunciator of a discuss that is constructed by multiple voices that contribute to its construction. Since this role is identified, the analysis turns to the characteristics of the scientific information inside it.